POTENSI AZOLLA SEBAGAI SUBSTITUSI PUPUK KANDANG PADA BUDIDAYA PADI ORGANIK - Jauhari Syamsiyah; Bambang Hendro Sunarminto; Mujiyo Mujiyo (Caraka Tani: Journal of Sustainable Agriculture, 2016)
One of problems faced by farmers in the rice cultivation with organic system is organic fertilizer limited, especially for farmers who do not have livestock. Azolla is one of materials that can be used as organic fertilizer. The aim of the research was to determine whether Azolla (Azolla mycrophylla L.) is able to meet the nutrient needs of some rice varieties on organic rice cultivation. The experiment used factorial complete randomized block design with three factors and three replications. Azolla was spread at days after transplanting and at 25 days after transplanting, 75% of Azolla was incorporated into soil and the rest was left up until rice were harvested. Meanwhile, cow manure was distributed after tillage. The treatment consisted of rice varieties (Mira1, Mentik Wangi and Red and White), Azolla (0 and 2 tons / ha) and manure (0 and 10 tons / ha). The result showed that Azolla did not significantly increase growth and yield of rice, despite it could increase the  N uptake 5,4% and P uptake P 17,3% , weight of dry straw, dry grain and 1,000 seeds by 5,86%, 12.7%, 7.37% than without Azolla respectively. Azolla 2 tons/ha with manure 10 tons/ha were able to increase N uptake by 7.6%, the uptake P by 13.7% and the of productive tiller number by 9.88%. From the standpoint of crop yields with organic system, a single use of Azolla has not been able to replace manure.